12-month effects of incretins versus SGLT2-Inhibitors on cognitive performance and metabolic profile. A randomized clinical trial in the elderly with Type-2 diabetes mellitus - Perna S (Dove Medical Press, 2018)
Simone Perna,1 Manuela Mainardi,2 Paolo Astrone,2 Carlotta Gozzer,3 Anna Biava,1 Ruben Bacchio,3 Daniele Spadaccini,3 Sebastiano Bruno Solerte,2 Mariangela Rondanelli4 1Department of Biology, College of Science, University of Bahrain, Sakhir Campus, Kingdom of Bahrain; 2University of Pavia, Department of Internal Medicine, Section of Geriatrics and Gerontology, Azienda di Servizi alla Persona “Istituto Santa Margherita”, Pavia, Italy; 3University of Pavia, Department of Public Health, Experimental and Forensic Medicine, Section of Human Nutrition, Endocrinology and Nutrition Unit, Azienda di Servizi alla Persona ‘‘Istituto SantaMargherita’’, Pavia, Italy; 4IRCCS Mondino Foundation, Pavia, Department of Public Health, Experimental and Forensic Medicine, Unit of Human and Clinical Nutrition, University of Pavia, Italy Aim: The aim of the present study is to examine the effects on cognitive performance, anthropometric measures, and metabolic markers in 2 different treatments: Incretins vs sodium-glucose co-transporter-2 inhibitors (SGLT2-I). Materials and methods: A randomized controlled clinical trial was carried out on 39 elderly subjects (23 men and 16 women) with type 2 diabetes mellitus, with a mean age of 77.21±8.07 years. Body mass index (BMI) of 29.92±4.31 kg/m2 and a cognitive status measured by a Mini Mental State Examination (scores >27 points). The subjects were on a 3-month treatment with a maximal dose of metformin as a stable regime, with the addition of incretins (liraglutide at doses of up to 1.8 mg/d; vildagliptin at 100 mg/d; sitagliptin 100 mg/d; and linagliptin 5 mg/d), or SGLT2-I (canagliflozin 300 mg/d; empagliflozin 25 mg/d; and dapagliflozin 10 mg/d). Glucose control was monitored by fasting glucose and glycosylated hemoglobin. Cognitive performance (by way of Verbal Fluency Test, Attentive Matrices Test, and Babcock Story Recall Test), anthropometric measures, and plasma lipids were also evaluated. Results: Cognitive status did not change significantly during the 12 months of treatment in either group: Verbal Fluency Test: (SGLT2-I: P=1.00, incretins: P=0.598); Babcock Story Recall Test (SGLT2-I: P=0.391; incretins: P=0.351); and Attentive Matrices Test (SGLT2-I: P=0.679, incretins: P=0.901). SGLT2-I also resulted in a reduction in weight (–1.95 kg; P<0.05), in BMI (–0.69 kg/m2; P<0.05) and an increase in high-density lipoprotein cholesterol (+5.73 mg/dl; P<0.01). Conclusion: Preliminary data show that patients treated with incretins and SGLT2-I have not suffered a reduction in cognitive performance during the 1 year of treatment. Metabolic outcome seemed to benefit, in particular, in patients who were treated with SGLT2-I. Keywords: SGLT-2 inhibitors, incretins, cognitive performance, cognitive impairment, metabolic outcome